Xylitol for the prevention of acute otitis media episodes in children aged 2–4 years: protocol for a pragmatic randomised controlled trial. Issue 8 (5th August 2018) - Persaud, Nav; Laupacis, Andreas; Azarpazhooh, Amir; Birken, Catherine; Hoch, Jeffrey S; Isaranuwatchai, Wanrudee; Maguire, Jonathan L; Mamdani, Muhammad M; Thorpe, Kevin; Allen, Christopher; Mason, Dalah; Kowal, Christine; et al.
Abstract : Introduction: Xylitol (or 'birch sugar') is a naturally occurring sugar with antibacterial properties that has been used as a natural non-sugar sweetener in chewing gums, confectionery, toothpaste and medicines. In this preventative randomised trial, xylitol will be tested for the prevention of acute otitis media (AOM), a common and costly condition in young children. The primary outcome will be the incidence of AOM. Secondary outcomes will include upper respiratory tract infections (URTIs) and dental caries. Methods and analysis: This study will be a pragmatic, blinded (participant and parents, practitioners and analyst), two-armed superiority, placebo-controlled randomised trial with 1:1 allocation, stratified by clinical site. The trial will be conducted in the 11 primary care group practices participating in the TARGet Kids! research network in Canada. Eligible participants between the ages of 2–4 years will be randomly assigned to the intervention arm of regular xylitol syrup use or the control arm of regular sorbitol use for 6 months. We expect to recruit 236 participants, per treatment arm, to detect a 20% relative risk reduction in AOM episodes. AOM will be identified through chart review. The secondary outcomes of URTIs and dental caries will be identified through monthly phone calls with specified questions. Ethics and dissemination: Ethics approval from the Research Ethics Boards at the Hospital for Sick Children and St. Michael's Hospital has been obtained for this study and also for the TARGet Kids! research network. Results will be submitted for publication to a peer-reviewed journal and will be discussed with decision makers. Trial registration number: NCT03055091 ; Pre-results.